Modifications of Human Subcutaneous ADMSC after PPARγ Activation and Cold Exposition - Diana Vargas; Wendy Rosales; Fernando Lizcano (Hindawi Limited, 2015)
Mesenchymal stem cells are a diverse population of cells with a wide range of potential therapeutic applications. In particular, cells from adipose tissue have the distinction of being easily accessible and contain a lot of stem cells. ADMSCs can be induced to mature adipocyte and activate the energy expenditure upon treatment with total PPARγ agonists. Additionally these cells may respond to cold by activating the thermogenic program. In the present study, we determined the effect of partial agonism of PPARγ and temperature reduction on phenotype and metabolic activity of ADMSCs from human adipose subcutaneous tissue. We found that adipocytes differentiated with total and partial agonists of PPARγ and exposed to 31°C are able to respond to cold significantly increasing the expression of thermogenic proteins such as UCP1, PGC1α, and CITED1, a marker of beige phenotype. Additionally, we found that adipocyte cells subjected to cold had a reduction in triglycerides and increased adiponectin levels. These data confirm the promising role of ADMSCs as a treatment for metabolic disorders since it is possible to induce them to mature adipocytes and modulate their phenotype toward a cell with high-energy expenditure and metabolic beneficial effect.